Lévy noise effects on Josephson junctions. (December 2021) - Guarcello, C.
Abstract: We review three different approaches to investigate the non-equilibrium stochastic dynamics of a Josephson junction affected by Lévy-distributed current fluctuations. First, we study the lifetime in the metastable superconducting state of current-biased short and long junctions, in the presence of Gaussian and Lévy noise sources. We highlight the noise-induced nonmonotonic behavior of the mean switching time as a function of noise intensity and driving frequency, that is the noise enhanced stability and the stochastic resonant activation, respectively. Then, we characterize the Lévy noise source through the average voltage drop across a current-biased junction. The voltage measurement versus the noise intensity allows to infer the value of the stability index that characterizes Lévy-distributed fluctuations. The numerical calculation of the average voltage drop across the junction well agrees with the analytical estimate of the average velocity for Lévy-driven escape processes from a metastable state. Finally, we look at the distribution of switching currents out of the zero-voltage state, when a Lévy noise signal is added to a linearly ramped bias current. The analysis of the cumulative distribution function of the switching currents gives information on both the Lévy stability index and the intensity of fluctuations. We present also a theoretical model to catch the features of the Lévy signal from a measured distribution of switching currents. The phenomena discussed in this work can pave the way for an effective and reliable Josephson-based scheme to characterize Lévy components eventually embedded in an unknown noisy signal.